Hubungan Antara Lama Mengemudi Dengan Terjadinya Nyeri Punggung Bawah Miogenik Pada Sopir Bus di Terminal Tirtonadi - Wibowo, Achmad Sugiarto, Wahyuni, SSt.FT.M.Kes, Agus Widodo, S.Fis, M.Kes (2016)
Background : Low back pain (LBP) is pain felt in the lower back area with the primary symptoms of pain or feeling discomfort in the lower back area and the surrounding bone. Pain usually arises as a result of factors that work using long sitting position and maintain posture while working, workers who need a sitting position for a long time is the bus driver. Purpose : This study aims to know the relationship between long drive in the lower back pain miogenic on the bus driver in the Terminal Tirtonadi. Aim of Research: To giving information to the bus driver that the work is in the rest could potentially result in lower back pain so that workers can anticipate and make efforts to prevention and improvement in the work place. Research Method : This research was using observational research and with the cross sectional approach. The sampling techniques used purposive sampling using purposive sampling with a 73 people as respondents. The measure is used in this study uses the interview with a questionnaire, REBA ( Rapid Entire Body Assessment ) and ODI ( Oswestry Disability Index ). This study using the statistics which is chi-square. Result : The value of the test at the table 4.13 get the value of <0,5 which has a significant pain p=0,001 and for the table 4.14 get the value of <0,5 which has a value of signification the pain p=0,024 which means there is a long drive with low back pain. Conclusion : There is a relationship between the long drive in the lower back pain miogenic in the bus in Terminal Tirtonadi. Kata kunci : long driving, Low back pain (LBP).